Management Of Madrasah Research Development In Enhancing Educational Competitiveness - Laili Nikmah; Ahmad Tanzeh; Sulistyorini (International Journal of Education Management and Religion, 2026)
This study aims to analyze the management of research madrasah program development in enhancing educational competitiveness at MTsN 2 Kota Kediri and MTsN 1 Kota Malang. The study employed a descriptive qualitative approach with a multi-site study design. Data were collected through in-depth interviews, participatory observation, and documentation, and were analyzed using the Miles and Huberman model, which includes data reduction, data display, and conclusion drawing. The findings reveal that the development of the research madrasah program was carried out through four main stages: planning, implementation, evaluation, and institutionalization. During the planning stage, the madrasahs mapped the potential of teachers and students and established a research development team. The implementation stage was conducted through strengthening facilities, project-based learning, and the cultivation of a research culture. The evaluation stage was continuously carried out through monitoring, supervision, and program achievement assessment. Meanwhile, the institutionalization stage was realized through scientific publication, strengthening external networks, and developing a research-based academic culture. The study found that the research madrasah program was able to improve learning quality, academic achievement, scientific culture, and public trust in madrasahs. Therefore, the research madrasah program has become an effective strategy for sustainably enhancing the educational competitiveness of madrasahs.